Mental health support need among health care workers post needle stick injuries: a sequential mixed method study - Sami, Muhammad; Sana (Journal of the Pakistan Medical Association, 2026)
Objective: To measure anxiety and stress levels among healthcare workers having experienced needlestick injury, and to explore their perceived necessity of mental health support services. Method: The sequential mixed-method study was conducted from July to December 2024 at Hayatabad Medical Complex, Peshawar, Pakistan, and comprised healthcare workers of either gender who had experienced needlestick injury during the preceding one month. Data was collected using the Beck Anxiety Inventory and the Perceived Stress Scale, while qualitative insights were obtained through in-depth interviews. Data was analysed using SPSS 27. Results: Of the 199 healthcare workers, 118(59.3%) were male and 81(40.7%) were female. The overall mean age was 34.61±5.53 years. There were 86(43.22%) participants who had experienced severe anxiety, and 103(51.76%) participants reported high levels of perceived stress. Age, job role and hepatitis B vaccination status significantly influenced anxiety, while stress levels were associated with age and hepatitis B vaccination status (p<0.05). Thematic analysis highlighted the emotional toll, coping strategies, and a general lack of awareness. The participants unanimously favoured mental health support services. Conclusion: Needlestick injuries were found to significantly impact the psychological wellbeing of healthcare workers, underscoring the need for comprehensive mental health support services. Key Words: Needle stick injuries, Healthcare workers, Mental health, Anxiety disorders, Stress, Psychological.